THE EFFECT OF PEER-TO-PEER LOANS ON PERFORMANCE MEDIATED BY FINANCIAL LITERACY - Dina Rosmanelian; Syaifuddin Syaifuddin; Nagian Toni (Journal of Development Economics and Digitalization, Tourism Economics, 2026)
Lack of understanding regarding financial management traders has caused many MSMEs to close down. This research contributes to the growing literature on digital finance and MSME management by demonstrating that financial literacy acts as a mediating variable in the relationship between peer-to-peer (P2P) lending utilization and MSME performance. These findings expand the conceptual model, which has focused primarily on the direct impact of financing access on business performance, by demonstrating that the effectiveness of digital financing is significantly influenced by MSMEs' ability to understand, manage, and appropriately utilize financial resources. This study uses an explanatory research approach and in-depth literature study. This study employed a literature review as a data analysis method. The data sources used in this study consisted of secondary data. The data collection technique employed a comparison of research data from various journals and related sources. The results of this study indicate that peer-to-peer lending has a positive and significant effect on performance. Peer-to-peer lending also has a positive and significant effect on financial literacy of MSMEs in North Sumatra. Meanwhile, financial literacy has a positive and significant effect on MSME performance. In the indirect hypothesis, it was found that financial literacy mediates the influence between peer-to-peer lending and MSME performance. Therefore, it can be said that all variables influence the sustainability of MSMEs in North Sumatra.